Pengaruh Pendidikan Kesehatan pada Audio Visual dengan Visual pada Deteksi Dini Kanker Serviks Melalui Pemeriksaan IVA Pengetahuan dan Sikap Ibu di Hinai Kiri Puskesmas Kecamatan Secanggang Kabupaten Langkat Tahun 2018: The Effect of Health Education on Audio Visual with Visual on Early Detection of Cervical Cancer Through IVA Examination of Knowledge and Mother's Attitude at Hinai Kiri Puskesmas Kecamatan Secanggang Kabupaten Langkat Tahun 2018 - SRI NURNILAWATI (LPPM - STIKES Pemkab Jombang, 2020)
Cervical cancer is a malignant disease in cervix; it ranks the second as the cause of death in women throughout the world after breast cancer. The coverage of its early detection, using IVA method in Indonesia is 8.1% so that the case is found when it has already been in advanced stage. IVA (Visual Inspection with Acetic Acid) is a simple alternative method which is aimed to detect cervical cancer early as possible. The objective of the research was to find out the influence of audiovisual media health education with visual media about cervical cancer early detection through IVA screening on women’s knowledge and attitude at Hinai Kiri Puskesmas. The research used quasi experimental method with without control group design. The samples were 24 married women who were 30-50 years old, taken by using purposive sampling technique. The data were analyzed by using bivariate analysis with paired t-test statistic test. The result of paired t-test showed that p-value = 0.000 (p<0.05) in the respondents’ knowledge and attitude with the increase in the mean-score of the knowledge with audiovisual media was -16.75, visual media was -13.42, and the mean-score of attitude with audiovisual media was -18.83, visual media was -20..34. There was the influence of health education of audiovisual media with visual media on the respondents’ knowledge and attitude toward cervical cancer early detection through IVA screening. It is recommended that health education technique be developed to increase people’s awareness of cervical cancer, and cervical cancer screening facility be provided by using affordable IVA method.